Tax Competition with Heterogeneous Capital Mobility - Steeve Mongrain; John D. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2015)
An ongoing debate in the tax competition literature is the desirability for a system of countries, or regions, to restrict the preferential treatment of different forms of capital. A widespread belief is that without such restrictions, countries would aggressively compete for mobile capital, resulting in taxes that are far below their desirable level. We further investigate this question by departing from the bulk of the literature in three important ways. First, we assume that in addition of caring about tax revenue, countries also care about private sector income. Second, firms are distinguished by their country of origin. Finally, we consider both identical countries and countries that differ in size. We demonstrate how the relative desirability of the two tax regimes depends critically on country size differences and the distribution of moving costs. In some cases, preferential treatment is preferable. Large and small countries may also disagree about which regime is best.
Keywords: H73; H77; H71; 330; tax competition; heterogeneity; preferential tax treatment